KAJIAN KEABSAHAN JUAL BELI TANAH MENURUT PERATURAN PERUNDANG-UNDANGAN (STUDI PUTUSAN 40/PDT.G/2020/PN BKS) - Devana Mustika; Novina Sri Indiraharti (Reformasi Hukum Trisakti, 2022)
Land sales and purchases pursuant to Article 37(1) of PP Number 24 of 1997 must be done in front of the PPAT with documentation from the PPAT deed, but pursuant to Decision 40/Pdt.G/2020/Pn.Bks. The sale or purchase is not made prior to the PPAT and is only supported by a receipt. The issue at hand is whether Song Lung (Hendra Budiman) and Susiah Suprihatin's sale and purchase of land and buildings was legal and whether the judge's ruling on the legality of buying and selling land without a sale and purchase deed complied with statutory requirements. The secondary data employed in the normative legal research technique is descriptive in character and is Deductive conclusions are reached after qualitative analysis. The study's findings, analysis, and conclusion state that while the sale and purchase between Song Lung (Hendra Budiman) and Susiah Suprihatin is legal under customary law, it is invalid under the provisions of the PP Number 24 of 1997, specifically Article 37 paragraph (1), the PP Number 37 of 1998, specifically Articles 2 paragraphs (1) and (2), and the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of BPN Number 16 of 2021.